Potential of moringa leaves as antianemia for iron deficiency in white rat experiments - Hakim, Imam Lukmanul; Mulyani, Yani Mulyani; Yusransyah, Yusransyah (Institute of Computer Science (IOCS), 2024)
Iron deficiency anemiaa type of anemia that occurs due to the body lacking iron which results in a decrease in the number of red blood cells or hemoglobin in the blood which is insufficient for the body's physiological needs. In Indonesia, the prevalence of iron deficiency anemia is greatest in non-pregnant adult women, around 25-48% and pregnant women around 46-92%. According to several studies, Moringa leaves (Moringa oliefera) are a source of iron. Moringa leaves (moringa oliefera) are known to have various nutritional contents. one of which is iron, protein, vitamin A, Vitamin C, potassium and calcium. Moringa leaves are a plant that has quite a high iron content. The iron content in the body can help form hemoglobin and bind oxygen. This research aims to determine the potential of Moringa leaves as an anti-anemia. The reference search was carried out in the process of reviewing this article using the internet network via Pubmed, Sciencedirect and Google Scholar. National and international journals were obtained as primary data sources.From the data collected, Moringa leaves have the potential to increase hemoglobin levels in experimental white mice. The high amount of iron contained in Moringa leaves (Moringa oleifera) affects the increase in hemoglobin in the blood. This can be used as a reference for the use of Moringa leaves as an anti-anemia, both for prevention and treatment.